ANALASIS PENGELOLAAN PASAR RAKYAT DALAM MENINGKATKAN PENDAPATAN PEDAGANG PERSPEKTIF EKONOMI ISLAM (Studi Kasus di Desa Tebas Kuala Kecamatan Tebas) - Aryyesti, Mia; Sukmawati, U. Sulia; Apriani, Fitri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This people's market was built to control and increase the income of street vendors through market management. The focus of the problem in this study is how to manage the People's Market in increasing the income of traders in Tebas Kuala Village, Tebas District and how to manage the Tebas People's Market in increasing the income of traders from an Islamic economic perspective. The aim is to find out how the management of the People's Market in increasing the income of traders in Tebas Kuala Village, Tebas District and to find out how the management of the People's Market in increasing the income of traders from an Islamic economic perspective. Based on the results of the study, it was concluded that the management of the Pasar Rakyat in increasing the income of traders in terms of development economic perspective is very good in its management, both in terms of facilities, cleanliness and security. The management carried out can increase the income of traders even though there is a lot of competition but with proper management the Pasar Rakyat Tebas has advantages over several other markets